1993
DOI: 10.1002/hep.1840180517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of small hepatocellular carcinoma in cirrhotic patients: A cohort study comparing surgical resection and percutaneous ethanol injection

Abstract: This study was intended to compare the survival rates of two contemporary cohorts of patients with solitary hepatocellular carcinomas < or = 4 cm subjected to surgical resection (n = 33) or percutaneous ethanol injection (n = 30). Outcomes in a third cohort, 21 patients with hepatocellular carcinoma who underwent orthotopic liver transplantation, were also assessed. Surgical and ethanol-treated patients were similar with regard to age and tumor stage, differing only in liver function; 30 of the 33 surgical pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
166
0
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(180 citation statements)
references
References 30 publications
7
166
0
7
Order By: Relevance
“…No RCTs have demonstrated that surgical resection is superior to percutaneous ablation. In nonrandomized comparative studies, hepatectomy was better than percutaneous ablation in one study [213] whereas others reported no significant difference between the two therapies [310][311][312]. Thus, it is difficult to conclude that surgical resection is the treatment of choice for resectable HCC.…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
“…No RCTs have demonstrated that surgical resection is superior to percutaneous ablation. In nonrandomized comparative studies, hepatectomy was better than percutaneous ablation in one study [213] whereas others reported no significant difference between the two therapies [310][311][312]. Thus, it is difficult to conclude that surgical resection is the treatment of choice for resectable HCC.…”
Section: Local Ablation Is a First-line Treatment Of Unresectable Smmentioning
confidence: 99%
“…We considered the 3-month mortality of partial hepatectomy to be 5%, ranging between 3% and 8%, considering that all patients had compensated cirrhosis. 3,17,[22][23][24] HCC Recurrence Rate After Partial Hepatectomy. The rate of recurrence of HCC after partial hepatectomy varies according to the different series and to the characteristics of the patients in each series.…”
Section: Proportion Of Patients With Hcc Developing Contraindicationsmentioning
confidence: 99%
“…[22][23][24][25] Patients with HCC were Abbreviations: HCC, hepatocellular carcinoma; OLT, orthotopic liver transplantation; TNM, tumor-node-metastasis classification system; pTNM, pathological tumor-nodemetastasis classification.…”
Section: Patientsmentioning
confidence: 99%